Elizabeth - Eccleston, Christopher; Attenborough, Richard; Hirst, Michael; Owen, Alison; Fellner, Eric; Bevan, Tim; Blanchett, Cate, 1969-; Rush, Geoffrey, 1951-; Fiennes, Joseph, 1970-; Gielgud, John, Sir, 1904-; Kapur, Shekhar, 1945-; Polygram Filmed Entertainment; et al. (New York : PolyGram Video, 1999)
Recounts the intrigues and intricacies of court life during the tumultuous early years of the reign of Queen Elizabeth I.
Originally produced as a motion picture in 1998.
Special features: director's commentary ; the making of Elizabeth ; Elizabeth featurette ; theatrical trailer and teaser ; cast and crew biographies ; photo gallery ; interactive menus.
Director of photography, Remi Adefarasin ; editor, Jill Bilcock ; original music by David Hirschfelder.
Cate Blanchett, Geoffrey Rush, Christopher Eccleston, Joseph Fiennes, John Gielgud, Richard Attenborough.
MPAA rating: R.
Soundtrack in English; subtitles in French or Spanish.
Keywords: Elizabeth -- I, -- Queen of England, -- 1533-1603 -- Drama; Man-woman relationships -- Drama; Video recordings for hard of hearing people; Great Britain -- History -- Elizabeth, 1558-1603 -- Drama; Biographical films; Historical films